2017
DOI: 10.1002/chem.201700829
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Phosphasilene Chemistry

Abstract: Heavier alkene analogues possess unique electronic properties and reactivity,e ncouraging multidisciplinary research groups to utilize them in the rational designo fn ovel classes of compounds and materials.P hosphasilenes are heavier imine analogues,c ontaining highly reactiveS i =P double bonds. Recent achievements in this field are closely related to the progress in the chemistry of stable low-coordinate silicon compounds. In this Review,w eh avea ttempted to summarize in ac omprehensive way the availabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 158 publications
3
30
0
2
Order By: Relevance
“…Moreover, 10 was characterized by X‐ray diffraction analysis (Figure ). The obtained spectroscopic and structural data of 10 are in good agreement with those of the previously described similar phosphasilene–NHC complex bearing a more bulky Dipp Ter aryl substituent at the silicon atom …”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, 10 was characterized by X‐ray diffraction analysis (Figure ). The obtained spectroscopic and structural data of 10 are in good agreement with those of the previously described similar phosphasilene–NHC complex bearing a more bulky Dipp Ter aryl substituent at the silicon atom …”
Section: Figuresupporting
confidence: 88%
“…The obtained spectroscopic and structural data of 10 are in good agreement with those of the previously described similarp hosphasilene-NHC complex bearing am ore bulky Dipp Te ra ryl substituent at the silicon atom. [23,24] In summary,w eh ave synthesized and characterized the first donor-acceptor complexo fa na ryl silaaldehyde. Notably,i t reacts as am asked silacarbonyl, providing ana ccess to a number of stable derivatives, thus showingarelationship to carbonyl chemistry.D ifficulties in the preparation of the correspondingd onora nd acceptor-free silaaldehyde complexes, as well as the isolation of free spirosiloxane, underline the low stabilityo ft he corresponding free silaaldehyde.…”
mentioning
confidence: 99%
“…Selected examples of phosphasilenes (95-100). [72,73] Scheme 35. Synthesis of cyclic phosphasilene (103).…”
Section: Phosphagermenes (> Ge=pà )mentioning
confidence: 99%
“…The existence of Si=P double bond in 95 was established by using spectroscopic methods. After this discovery, several research groups independently reported the synthesis of phosphasilenes depicted in Figure 5 ( 96 – 100 ) [72b–f,73] …”
Section: Heteronuclear Multiple Bondmentioning
confidence: 99%
“…Im Hinblick auf die Schlüsselrolle des Phosphors als N‐Dotierungselement in der Silicium‐Halbleiterindustrie ist die Kombination dieser beiden Elemente auf molekularer Ebene von besonderem Interesse: Erste Berichte über die spektroskopische (Bickelhaupt, 1984) und strukturelle Charakterisierung (Niecke, 1993) stabiler, acyclischer Phosphasilene mit einer Si=P‐Doppelbindung ebneten den Weg für weitere Durchbrüche hinsichtlich Synthese und Reaktivität . Kürzlich kamen stabile Silylen‐Basen‐Addukte als Vorstufen für Donor‐stabilisierte und damit ylidische Si=P‐Bindungen mit einem tetrakoordinierten Siliciumatom zum Einsatz . Unsere Gruppe berichtete über die 1,3‐Migration der Aminogruppe in intermediären P ‐Aminophosphino‐Disilenen als gut geeignetes synthetisches Protokoll .…”
Section: Figureunclassified